Simulation of the in-plane structural behavior of unreinforced masonry walls and buildings using DEM - Pulatsu, Bora (2020)
In this study, a novel computational modeling strategy is proposed to estimate the lateral load capacity and behavior of unreinforced masonry (URM) structures. All commonly noted failure mechanisms are captured via the proposed modeling strategy using the discrete element method (DEM) in three-dimensions (3D). Masonry walls are represented as a system of elastic discrete blocks, where the nodal velocities are evaluated by integrating the equations of motion using the central difference method. Then, the mechanical interactions among adjacent blocks are examined utilizing the relative contact displacements and employed in the contact stress calculation. Through this research, a new stress-displacement contact constitutive model is considered and implemented in the commercial software 3DEC, which includes softening stress-displacement behavior for tension, shear, and compression along with the fracture energy concept. The results of the discontinuum models are validated on small- and large-scale experimental studies available in the literature with good agreement. Furthermore, important inferences are made regarding the effect of block size, the number of contact points, and contact stiffness values for robust and accurate simulations of masonry walls.